1999
DOI: 10.1074/jbc.274.46.32943
|View full text |Cite
|
Sign up to set email alerts
|

The Tetrameric Protein Transthyretin Dissociates to a Non-native Monomer in Solution

Abstract: In amyloidosis, normally innocuous soluble proteins polymerize to form insoluble fibrils. Amyloid fibril formation and deposition have been associated with a wide range of diseases, including spongiform encephalopathies, Alzheimer's disease, and familial amyloid polyneuropathies (FAP). In certain forms of FAP, the amyloid fibrils are mostly constituted by variants of transthyretin (TTR), a homotetrameric plasma protein implicated in the transport of thyroxine and retinol. The most common amyloidogenic TTR vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
132
1
2

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(144 citation statements)
references
References 26 publications
9
132
1
2
Order By: Relevance
“…Each TTR monomer contains eight strands that form two sheets of four strands each and are arranged in a topology similar to the classic Greek key barrel. However, TTR fibrils are not likely to be made up of the native tetrameric form, and transition may occur in which monomers are modified into a pathological conformation (Quintas et al, 1999;Sebastiã o et al, 1998). Bearing in mind other described ligands for RAGE (A␤, amylin, serum amyloid A, and prion protein) and the high ␤ sheet content of TTR, this seems to indicate that this receptor is prone to recognize ␤ sheet structures, which, in the case of TTR, might be present in both the soluble and fibrillar form.…”
Section: Sousa Et Almentioning
confidence: 99%
“…Each TTR monomer contains eight strands that form two sheets of four strands each and are arranged in a topology similar to the classic Greek key barrel. However, TTR fibrils are not likely to be made up of the native tetrameric form, and transition may occur in which monomers are modified into a pathological conformation (Quintas et al, 1999;Sebastiã o et al, 1998). Bearing in mind other described ligands for RAGE (A␤, amylin, serum amyloid A, and prion protein) and the high ␤ sheet content of TTR, this seems to indicate that this receptor is prone to recognize ␤ sheet structures, which, in the case of TTR, might be present in both the soluble and fibrillar form.…”
Section: Sousa Et Almentioning
confidence: 99%
“…Because stabilizing the tetrameric forms of TTR has been reported to prevent amyloid formation, 10 we used non-boiled SDS-PAGE to determine the effect of albumin on the stability of TTR tetramers. Figure 2 shows that albumin stabilized the …”
Section: Effect Of Albumin On the Stability Of Tetrameric Forms Of Ttrmentioning
confidence: 99%
“…9 It has been proposed that tetrameric TTR is not itself amyloidogenic, but that dissociation of the tetramer into a compact non-native monomers with low conformational stability can lead to amyloid fibril formation. 10 The rate of TTR tetramer dissociation, which is believed to be the rate-limiting step in amyloid fibril formation, is strongly influenced by point mutations in the TTR gene. 11 In addition, post-translational modification of TTR is also thought to have a key role in amyloid fibril formation.…”
mentioning
confidence: 99%
“…Several amyloidogenic variants have their crystal structure determined and while some of them do not show signi¢cant di¡erences from the wild-type (WT) protein, others point to a transmission of structural events, associated with the mutation, which destabilize the quaternary protein structure. It is current opinion that the modi¢ed TTR represents an amyloidogenic intermediate, which integrates the ¢-bril structure [3]; analyses of FAP ¢brils have proved that TTR in the ¢brils maintains a L-conformation and suggested that the TTR monomer is the building block in ¢brils [4]. Further studies on native and synthetic TTR ¢brils using high-resolution structural techniques will further elucidate ¢-bril structure and the aggregation pathway.…”
Section: Introductionmentioning
confidence: 99%